General approaches to creating a mathematical model of a synchronous reactive motor with permanent magnets for electric transport - Shtompel, O. M. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article considers promising methods for creating mathematical models of traction synchronous-reactive motors with permanent magnets, which makes it possible to take into account the geometric parameters of the location of magnets in the motor excitation system. According to the results of numerical experiments on the calculations of the magnetic field by the finite element method in the plane-parallel formulation of the problem and subsequent regression analysis, five-dimensional polynomial dependences of the derivatives of flux linkages and torque on current and angular coordinate were obtained, which make it possible to identify a generalized mathematical model of a synchronous reactive traction motor, both with a non-sectioned and sectioned rotor, for a metro car. When conducting regression analysis, a rational order of the function approximating the flux linkage of the motor phases and its derivatives, as well as the electromagnetic torque, was determined.

Стаття розглядає перспективні методи щодо створення математичних моделей тягових синхронно-реактивних двигунів з постійними магнітами, яка надає можливість врахування геометричних параметрів розташування магнітів у системі збудження двигуна. За результатами чисельних експериментів щодо розрахунків магнітного поля методом скінчених елементів у плоскопаралельній постановці задачі і подальшого регресійного аналізу отримано п'ятивимірні поліноміальні залежності похідних потокозчеплень та моменту за струмом та кутовою координатою, які дають можливість ідентифікувати узагальнену математичну модель синхронного реактивного тягового двигуна, як з несекціанованим так і секціанованим ротором, для метровагону. При проведені регресійного аналізу визначено раціональний порядок функції, що апроксимує потокозчеплення фаз двигуна та його похідних, а також електромагнітного моменту.
Загальні підходи до створення математичної моделі синхронно-реактивного двигуна з постійними магнітами для електротранспорту
Keywords: traction motors; permanent magnets; electric transport; excitation systems; flux linkages; polynomial dependences; тягові двигуни; постійні магніти; електротранспорт; системи збудження; поліноміальні залежності; потокозчеплення